Eosinophilic angiitis presenting with a true, fusiform, temporal artery aneurysm - MacDiarmid, Megan (Clin Case Rep, 2017)
Temporal artery aneurysm is a rare cause of temporal artery swelling in the absence of preceding trauma. Vasculitis other than giant cell arteritis, such as eosinophilic granulomatosis with polyangiitis, should be considered in such cases and a careful assessment of other medium‐sized arteries undertaken.